Digitalised measures for the prevention of central line-associated bloodstream infections: a scoping review - Basilice Minka Obama; Rebecca Grant; Stephan Harbarth; Niccolò Buetti; Gaud Catho (Antimicrobial Resistance and Infection Control)
Abstract Background Central line-associated bloodstream infections (CLABSI) increase morbidity, mortality, and healthcare costs of hospitalised patients, despite being largely preventable. While evidence-based guidelines for preventing CLABSI are well-established, the implementation of these measures remain suboptimal. Digitalization presents a promising approach to improve guideline adherence, streamline implementation processes, and ultimately reduce CLABSI rates. Methods This scoping review aims to synthesize the available evidence on digitalised interventions for the prevention of CLABSI. A systematic search was conducted using Medline to identify studies published between January 1, 2014, and March 20, 2024, that reported on the implementation of digitalised preventive measures for CLABSI and evaluated their impact on CLABSI rates. Data extraction included study characteristics, features of the digitalised preventive measures, effectiveness in reducing CLABSI rates, and relevant process outcomes. Results A systematic search yielded 263 articles, of which six studies were included. Digitalised interventions were predominantly designed for use by nurses in tertiary-level hospitals (n = 6), primarily in intensive care units (n = 5) and targeted pediatric patient populations (n = 5). These measures were often implemented as part of multimodal strategies. The digital interventions included hospital dashboards (n = 2), mobile applications (n = 2), automatic notifications of catheter days (n = 1), and e-learning modules with electronic reminders (n = 1). The most common study design was quasi-experimental without an external control group. All included studies reported a reduction in CLABSI rates, ranging from 21 to 73%. Healthcare workers generally perceived these digital interventions positively. Discussion Digitalised interventions for CLABSI prevention seem to be effective in reducing infection rates, likely because of increasing compliance to established guidelines for CLABSI prevention.